Научные подходы в прогнозировании развития производства - Жадан, Татьяна Андреевна (НТУ "ХПИ", 2004)
Рекомендовано в прогнозуванні розвитку виробництва у промисловості використання наукових підходів. Проведена їх класифікація в залежності від мети дослідження.

Use of the scientific approaches is offered in forecasting development of manufacture in an industry. Their classification is carried out depending on the purpose of research.
Keywords: прогнозирование; производство; научные подходы; прогнозирование развития производства; виды научных подходов